2007
DOI: 10.1016/j.micinf.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein e (P4) of Haemophilus influenzae: role in heme utilization and pathogenesis

Abstract: Lipoprotein e (P4) of Haemophilus influenzae is a phosphomonoesterase, encoded by the hel gene, that has been implicated in the acquisition of heme by this fastidious organism. However, lipoprotein e (P4) is also involved in the utilization of NAD and NMN. Some reports have concluded that the reported heme-related growth defect actually reflects a growth defect for NAD. In the current study hel insertion mutants were constructed and a role for e (P4) in heme acquisition was demonstrated independent of its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…Type IV pili are important for nasopharyngeal colonization and in vivo growth of H. influenzae [30], [35]. Since pilA is important for early biofilm formation, mono- and co-culture biofilms were grown for 4h and 24h and relative gene expression was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Type IV pili are important for nasopharyngeal colonization and in vivo growth of H. influenzae [30], [35]. Since pilA is important for early biofilm formation, mono- and co-culture biofilms were grown for 4h and 24h and relative gene expression was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…In H. influenzae , lipoprotein E is essential for hemin uptake and the utilization of Nicotinamide adenine dinucleotide [45], [88], [89]. As A. pleuropneumoniae biotype-1 is also dependent on exogenous sources of Nicotinamide adenine dinucleotide for growth [90], lipoprotein E could also be relevant for the pathogenesis of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that dsbA is required for H. influenzae bacteremia caused by both unencapsulated strain Rd and a virulent encapsulated type b strain. Heme uptake is required for aerobic growth of H. influenzae, which cannot synthesize the porphyrin ring (24,70), and several heme utilization pathways have been implicated in bloodstream infection by H. influenzae (47,61). We demonstrate that the heme transport protein, HbpA, contains a DsbA-dependent disulfide bond.…”
mentioning
confidence: 84%